2018
DOI: 10.1158/0008-5472.can-17-2870
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective MRCK Inhibitors with Therapeutic Effect on Skin Cancer

Abstract: The myotonic dystrophy-related Cdc42-binding kinases MRCKα and MRCKβ contribute to the regulation of actin-myosin cytoskeleton organization and dynamics, acting in concert with the Rho-associated coiled-coil kinases ROCK1 and ROCK2. The absence of highly potent and selective MRCK inhibitors has resulted in relatively little knowledge of the potential roles of these kinases in cancer. Here, we report the discovery of the azaindole compounds BDP8900 and BDP9066 as potent and selective MRCK inhibitors that reduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 56 publications
3
67
0
Order By: Relevance
“…Although the molecular mechanisms underlying MRCK activation are not fully understood, Cdc42/Rac1 binding, membrane localization and the release of auto-inhibitory interactions appear to be required for MRCK signaling (Leung et al, 1998;Unbekandt and Olson, 2014;Zhao and Manser, 2015). Recent identification of an autophosphorylation site in MRCKα at Ser1003 led to the development of a phospho-site specific MRCKα antibody that can be used to assess levels of MRCKα activation and will likely prove useful for the further elucidation of MRCKα activation mechanisms (Unbekandt et al, 2018). Autophosphorylation of MRCKβ at Thr1108 can be used as a readout of MRCKβ kinase activity, although attempts to develop a suitable antibody tool have so far been unsuccessful (Unbekandt et al, 2019).…”
Section: Myotonic Dystrophy Kinase-related Cdc42-binding Kinases (Mrcks)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the molecular mechanisms underlying MRCK activation are not fully understood, Cdc42/Rac1 binding, membrane localization and the release of auto-inhibitory interactions appear to be required for MRCK signaling (Leung et al, 1998;Unbekandt and Olson, 2014;Zhao and Manser, 2015). Recent identification of an autophosphorylation site in MRCKα at Ser1003 led to the development of a phospho-site specific MRCKα antibody that can be used to assess levels of MRCKα activation and will likely prove useful for the further elucidation of MRCKα activation mechanisms (Unbekandt et al, 2018). Autophosphorylation of MRCKβ at Thr1108 can be used as a readout of MRCKβ kinase activity, although attempts to develop a suitable antibody tool have so far been unsuccessful (Unbekandt et al, 2019).…”
Section: Myotonic Dystrophy Kinase-related Cdc42-binding Kinases (Mrcks)mentioning
confidence: 99%
“…In a mouse model of SCC, topical application of BDP9066 reduced MRCKα activation in the skin and resulted in a decrease in tumor volume relative to controls. In a screen of 757 human cancer cell lines from 40 different cancer types, BDP8900 and BDP9066 treatment produced consistent anti-proliferative effects, suggesting MRCK may be a valid therapeutic target in a number of cancers other than SCC (Unbekandt et al, 2018). It is important to note that the toxicity of systemic BDP8900 and BDP9066 administration has not been studied and information regarding the bioavailability of these compounds is not yet available.…”
Section: Myotonic Dystrophy Kinase-related Cdc42-binding Kinases (Mrcks)mentioning
confidence: 99%
“…5B). Twice-daily dosing was chosen because, although the PK profile of BDP-9066 showed good bioavailability, rapid clearance was also observed (17). The compound was well tolerated, and PK analysis of blood taken at the time of culling confirmed its presence at micromolar concentrations ( Supplementary Fig.…”
Section: Pharmacologic Inhibition Of Mrck Inhibits Radiation-induced mentioning
confidence: 99%
“…This mode of invasion is characterized by an elongated cell body, actin-rich protrusions, and actinmyosin contractility at the rear of the migrating cells. Unbekandt and colleagues have recently demonstrated that MRCK can drive cancer cell migration, a process that can be inhibited by specific small-molecule inhibitors (15)(16)(17). Because CDC42 activity is upregulated in glioma (18,19) and may drive the mesenchymal mode of migration employed by infiltrating glioma cells, we investigated a potential role for MRCK-driven GBM cell invasion in the pathogenesis of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Except for EMT process, there are other mechanisms to explain for the increased invasive ability induced by irradiation (42,(54)(55)(56)(57)(58)(59)(60)(61), which are summarized in Table 2. But whether they have relationships with STAT3 is still unknown.…”
Section: Inhibiting Stat3 Decreased Radiation-induced Aggressive Behamentioning
confidence: 99%